2020
DOI: 10.1002/ece3.6377
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spleen transcriptomes of two wild rodent species reveals differences in the immune response against Borrelia afzelii

Abstract: Different host species often differ considerably in susceptibility to a given pathogen, but the causes of such differences are rarely known. The natural hosts of the tick‐transmitted bacterium Borrelia afzelii, which is one of causative agents of Lyme borreliosis in humans, include a variety of small mammals like voles and mice. Previous studies have shown that B. afzelii‐infected bank voles (Myodes glareolus) have about ten times higher bacterial load than infected yellow‐necked mice (Apodemus flavicollis), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…The present results are similar to the findings of a previous study, where the spleen transcriptome analyses of B. afzelii -infected and uninfected bank voles ( Myodes glareolus ) and yellow-necked mice ( Apodemus flavicollis ) were performed ( Zhong et al., 2020 ). Although both animal species are considered natural reservoir hosts of B. afzelii in Europe ( Zhong et al., 2019 ), Borreliella -infected bank voles have on average a magnitude higher spirochetal loads in their tissues ( Raberg, 2012 ; Zhong et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results are similar to the findings of a previous study, where the spleen transcriptome analyses of B. afzelii -infected and uninfected bank voles ( Myodes glareolus ) and yellow-necked mice ( Apodemus flavicollis ) were performed ( Zhong et al., 2020 ). Although both animal species are considered natural reservoir hosts of B. afzelii in Europe ( Zhong et al., 2019 ), Borreliella -infected bank voles have on average a magnitude higher spirochetal loads in their tissues ( Raberg, 2012 ; Zhong et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although both animal species are considered natural reservoir hosts of B. afzelii in Europe ( Zhong et al., 2019 ), Borreliella -infected bank voles have on average a magnitude higher spirochetal loads in their tissues ( Raberg, 2012 ; Zhong et al., 2019 ). The comparative analyses between infected and uninfected animals within each species identified only 8 and 5 DEGs in B. afzelii -infected bank voles and yellow-necked mice, respectively ( Zhong et al., 2020 ). Furthermore, similar to the current data, other study had also shown no significant involvement of inflammation or innate immunity genes, when transcriptomes of skin and blood samples taken at 5 weeks postinfection were compared between Bb strain Sh-2-82-infected and uninfected P. leucopus mice ( Long et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…De novo transcriptome assemblies contained 842,299 and 761,841 contigs for bank vole and yellow-necked mouse, respectively. A series of filtering steps resulted in the retention of 13,631 contigs and 13,744 contigs in bank vole and yellow-necked mouse, respectively (see Zhong et al 2020 for more details regarding de novo transcriptome assemblies). The orthology between bank vole and yellow-necked mouse genes was determined by Reciprocal Best Hit (RBH) via BLASTp, which resulted in 10,931 one-to-one orthologs.…”
Section: Resultsmentioning
confidence: 99%
“…In previous analyses of gene expression in spleen of wild-caught naturally B. afzelii -infected and uninfected bank voles and yellow-necked mice, we found that the two species respond in partly different ways to B. afzelii infection. Specifically, B. afzelii infection is associated with up-regulation of IFNα-signaling in yellow-necked mice, but down-regulation of IL6 signaling and the complement system pathway in bank voles ( Zhong et al 2020 ). These differences in immune response presumably contribute to the observed difference in B. afzelii infection intensity between the two species ( Råberg 2012 ; Strandh and Råberg 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation